Association of body size metrics with left atrial phasic volumes and reservoir function in the elderly. (20th October 2017) - Tugcu, Aylin; Russo, Cesare; Jin, Zhezhen; Homma, Shunichi; Nakanishi, Koki; Elkind, Mitchell S V; Rundek, Tatjana; Sacco, Ralph L; Di Tullio, Marco R
Abstract: Aims: General obesity, defined by increased body mass index (BMI), is associated with left atrial (LA) enlargement, a marker of cardiovascular risk in the general population. The association between abdominal adiposity, defined by increased waist circumference (WC) or waist-to-hip ratio (WHR), and LA phasic volumes and reservoir function is not well known. The aim of this study was to evaluate the association between different body size metrics and LA phasic volumes and reservoir function in the elderly. Methods and results: Participants from the CABL (Cardiovascular Abnormalities and Brain Lesions) study underwent measurement of BMI, WC, and WHR. The LA maximum (LAVmax ) and minimum (LAVmin ) volumes, and LA reservoir function, measured as total emptying volume index (LAEVI), total emptying fraction (LAEF), and expansion index (LAEI), were assessed by real-time 3D echocardiography. The study population included 629 participants (mean age 71 ± 9 years, 61% women). Mean BMI was 27.9 ± 4.6 kg/m 2, WC was 95.0 ± 11.7 cm, WHR was 0.91 ± 0.08. After adjusting for multiple potential confounders (demographics, cardiovascular risk factors, left ventricular mass index, and diastolic function), higher WC was significantly associated with higher LA phasic volumes (LAVmax, β = 0.10, P = 0.007 and LAVmin, β = 0.12, P = 0.002) and reduced reservoir function (LAEVI, β = −0.15, P = 0.001 and LAEI, β = −0.09, P = 0.027). WHR was significantly associated only with reduced reservoir function (LAEVI, β = −0.11, P = 0.012), whereas BMI was not associated with either LA phasic volumes or reservoir function. Conclusion: In the elderly, WC may have more impact on LA phasic volumes and reservoir function, and therefore risk for cardiovascular events, than WHR and BMI.